Plastic additives in commercial fish of Aegean and Ionian Seas and potential hazard to human health - Marmara, Dimitra; Brundo, Maria Violetta; Pecoraro, Roberta; Scalisi, Elena Maria; Contino, Martina; Sica, Carmen; Ferruggia, Greta; Indelicato, Stefania; Velardita, Rosario; Tiralongo, Francesco; Krasakopoulou, Evangelia (Frontiers in Marine Science, 2024)
Plastic additives include a wide range of pollutants, added throughout the production process of plastics aiming to improve their properties. Given that they are not chemically bound to the plastic items, they can easily migrate in the marine environment allowing their uptake by marine organisms and accumulation in their tissues. Representatives of Phthalic acid esters (PAEs) and bisphenols have been characterized for their ability to impact not only marine organisms but also humans via fish and seafood consumption. In this study, a liquid-liquid method was applied to determine the concentrations of selected PAEs and Bisphenol A (BPA) in the tissues of E.encrasicolus, S.pilchardus, B.boops, and M.barbatus from two important divisions of fisheries (North Aegean and the Western Ionian Seas, thereof NAS and IOS respectively) of the Mediterranean Sea. The level of contamination varied among the different species and geographical locations. DEHP (bis(2-ethylhexyl) phthalate) had the highest mean concentrations of the examined PAEs for all four species examined. Statistically significant differences in DEHP mean concentrations were observed between the tissues of B.boops (collected from NAS) and S.pilchardus (from IOS) (p < 0.05, Wilcoxon rank test). DIDP (di-isodecyl phthalate) was the following most common PAEs, although no statistically significant differences were presented between sites, species, and tissues. DINP (di-isononyl phthalate) was recorded only in the GIT of E.encrasicolus (from NAS), while the rest of the examined PAEs were presented in a smaller subset of the samples. Noticeably, the parent diester DBP and the metabolic monoester MNBP were concurrently detected in a part of the analyzed samples. The level of risk via fish consumption, based on the Estimated Daily Intake and the Target Hazard Quotient (THQ), showed that the PAEs and BPA had a low likelihood of a negative effect occurring for every scenario that was examined, although THQ for BPA indicated there was a higher likelihood than PAEs of an adverse effect to be presented. The results of this study highlighted the need for future efforts focusing on the factors affecting plastic additives occurrences in the marine environment, especially for marine organisms intended for consumption.